A test to evaluate the physical impact on technical performance in soccer - Rostgaard, T.; Iaia, F. M.; Simonsen, D. S.; Bangsbo, J. (The Journal of Strength and Conditioning Research, 2008)
The aim of the study was to develop and examine a test for evaluation of the physical and technical capacity of soccer players. Fourteen youth elite (YE) and seven sub-elite (SE) players performed a physical and technical test (PT-test) consisting of 10 long kicks interspersed with intense intermittent exercise. In addition, a control test (CON-test) without intense exercise was performed. In both cases, the test result was evaluated by the precision of the 10 kicks. The players also performed the Yo-Yo intermittent recovery test level 2 (Yo-Yo IR2). For the SE-players, blood samples were obtained and heart rate was measured before, during, and after the PT-test. A muscle biopsy was collected before and after the PT-test. Coefficient of variation for the PT- and CON-test was 11.7% and 16.0%, respectively. The YE-players performed better (P < 0.05) than the SE-players in both the PT-test (16.3 +/- 0.8 (+/-SE) vs. 13.2 +/- 1.3 points) and CON-test (24.4 +/- 0.7 vs. 20.5 +/- 1.6 points) with no difference in the relative PT-test result (PT-test/CON-test: 0.63 +/- 0.03 vs. 0.64 +/- 0.03). Summed performance of the first 5 repetitions was higher (P < 0.05) than for the last 5 repetitions (8.4 +/- 0.6 vs. 6.9 +/- 0.5; n = 20). The YE-players performed better (P < 0.05) than the SE-players during Yo-Yo IR2 (1023 +/- SE vs. 893 +/- SE m). The mean heart rate during the PT-test was 173 +/- 4 b.p.m. (90 +/- 2% of HRmax). Blood lactate, glucose, and ammonia reached 5.6 +/- 0.7, 6.2 +/- 0.6 mmol L-1, and 76 +/- 11umol L-1 at the end of the test, respectively. After the test muscle CP, glycogen and lactate was 52.9 +/- 6.6, 354 +/- 39, and 25.3 +/- 5.9 mmol kg-1 d.w., respectively. In summary, the PT-test can be used to evaluate a soccer player's technical skills under conditions similar to intense periods of a soccer game.